High performance architecture and grid computing International Conference, HPAGC 2011, Chandigarh, India, July 19-20, 2011. Proceedings - International Conference on High Performance Architecture and Grid Computing (Communications in computer and information science, 2011)
This book constitutes the refereeds proceedings of the International Conference on High Performance Architecture and Grid Computing, HPAGC 2011, held in Chandigarh, India, in July 2011. The 87 revised full papers presented were carefully reviewed and selected from 240 submissions. The papers are organized in topical sections on grid and cloud computing; high performance architecture; information management and network security. Theme - 1: Grid and cloud computing -- Theme - 2: High performance architecture -- Theme - 3: Information management and Network security